The Effects of Pandemic on Construction Industry in the UK - Shibani, Abdussalam; Hassan, Dyaa; Shakir, Nehal (Mediterranean Journal of Social Sciences, 2020)
Pandemics such as: Covid-19 virus have a major impact on the economy of the world and the construction industry has not been exempted. This research investigates the effects of pandemic on construction industry in the UK, and particularly, ways in which the UK construction industry stakeholders such as project managers, contractors, engineers and subcontractors have responded to these pandemics. The research involved a 30 study participants who comprised site engineers, project managers, construction teams, subcontractors and contractors. The findings reported construction companies both dealing with residential and commercial development were major affected by Covid-19 pandemic due to lockdown and social distancing in construction sites. The strategy that was applied by construction companies was maintaining a good relationship with their suppliers and the safety of construction teams. The findings of the research will offer construction companies in the UK insights on how to deal with such pandemics in future to become more resilient.